Regrowth capacity of Leucaena macrophylla Benth for dendroenergy purposes in Cortes, Honduras - Flores-Pinot, Daniel Abisai (2018)
The effect of cutting season, cutting height and sowing density in the management of Leucaena macrophylla Beneth regrowths was evaluated. We used an experimental plantation in Cortés, Honduras. The forest crop was evaluated at an age of one year and we used three planting densities (2500, 4445 and 10000 trees ha-1), three pruning treatments were applied within the design (control, 40 and 100 cm stump height), which were applied in the dry (March 2016) and rainy (July 2017). After the regrowth was cut, the mortality, type of regrowth, diameter growth and the height of the regrowth after one year were evaluated. The data revealed that there is no difference in the regrowth mortality rate as a function of the pruning season (average of 57.34 %), besides that regardless of the spacing and pruning height, the epicormic regrowth was the one that presented the highest presence. Regarding the diametric growth, variations were recorded between 1.2 and 4.3 cm and the variations in height from 0.5 to 5.8 m; In addition, a higher growth rate was found in the rainy season (15 to 35 % more than the dry season). No differences were found between the pruning at 40 and 100 cm and finally it was determined that a density of 1000 trees ha-1 negatively affected the growth of the plantation and generated growth decreases up to 20 % with respect to the densities of 4445 and 2500 trees ha-1, which did not show differences between them.